1984
DOI: 10.1210/endo-115-5-2026
|View full text |Cite
|
Sign up to set email alerts
|

ATRIAL NATRIURETIC FACTOR INHIBITS THE STIMULATION OF ALDOSTERONE SECRETION BY ANGIOTENSIN II, ACTH AND POTASSIUMIN VITROAND ANGIOTENSIN II-INDUCED STEROIDOGENESISIN VIVO.

Abstract: Since atrial natriuretic factor (ANF) blocks the contractile effect of angiotensin II on vascular strips, we investigated the action of the synthetic 48-73 ANF (previously called 8-33 ANF) on another target tissue of angiotensin II, the adrenal glomerulosa. ANF did not affect basal aldosterone output by isolated rat adrenal glomerulosa cells. ANF inhibited aldosterone secretion stimulated by 10(-8)M angiotensin II with an IC50 of 1.3 X 10(-9)M. Aldosterone secretion stimulated by 2.9 X 10(-10)M ACTH and by 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
3

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(72 citation statements)
references
References 0 publications
4
65
3
Order By: Relevance
“…Burnett et al (1986) also observed that whole kidney fractional delivery of sodium from the proximal tubule as estimated by the fractional excretion of lithium was increased. However, Baum and Toto (1986) Intravenous infusion of ANP resulted in significant decrease in PRA only at 30 min after the start of ANP infusion, while a significant decrease in PAC lasted even in the recovery period, which is consistent with previous studies using atrial extracts or atrial natriuretic factors (Burnett et al 1984;Chartier et al 1984;Maack et al 1984;Atarashi et al 1984Atarashi et al , 1985Campbell et al 1985). Our present results suggest that ANP suppresses PAC independent of inhibition of PRA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Burnett et al (1986) also observed that whole kidney fractional delivery of sodium from the proximal tubule as estimated by the fractional excretion of lithium was increased. However, Baum and Toto (1986) Intravenous infusion of ANP resulted in significant decrease in PRA only at 30 min after the start of ANP infusion, while a significant decrease in PAC lasted even in the recovery period, which is consistent with previous studies using atrial extracts or atrial natriuretic factors (Burnett et al 1984;Chartier et al 1984;Maack et al 1984;Atarashi et al 1984Atarashi et al , 1985Campbell et al 1985). Our present results suggest that ANP suppresses PAC independent of inhibition of PRA.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, atrial extract or atrial natriuretic peptide has been reported to suppress both renin secretion in dogs (Burnett et al 1984;) and aldosterone production in vitro (Atarashi et al 1984(Atarashi et al , 1985Chartier et al 1984;Campbell et al 1985). Therefore, another objective in the present study was to examine the effect of constant infusion of ANP on the reninaldosterone system in anesthetized rabbits.…”
mentioning
confidence: 93%
“…Furthermore, inhibition of aldosterone synthesis [2] and renin release have been well documented [3]. The peptides or probably their precursors are stored in specific secretory granules in mammalian atrial cardiocytes [4].…”
Section: Introductionmentioning
confidence: 99%
“…One of its target organs is the adrenal gland where the peptide inhibits aldosterone secretion from the zona glomerulosa cells (Chartier et al 1984;Atarashi et al 1984). A physiological influence of the peptide on adrenomedullary cells was indicated by data showing that human ANF binds to human pheochromocytoma cells, where it decreases catecholamine synthesis (Shionoiri et al 1987).…”
Section: Introductionmentioning
confidence: 99%